Strategic Transformation of the European Bunker Oil Industry : A Scenario Planning Perspective - Chavda, Bhautik Parshotambhai (2025)
This thesis responds to the rapid and fundamental transformation of the European bunker oil industry, driven by new climate regulations (e.g., EU ETS, FuelEU Maritime) and the pressure to decarbonize. It focuses on the strategic challenge of transitioning from heavy fuel oil to alternative fuels (LNG, biofuels, methanol, ammonia), which require substantial infrastructure investment and face commercial uncertainty. Based on industry analysis and real-world examples from major ports (Rotterdam, Antwerp), this research aims to develop clear strategies for European bunker suppliers. It investigates how they can successfully balance regulatory compliance, competitiveness, and innovation to navigate market consolidation and secure a profitable, low-carbon future in the maritime sector.